Stranger Months: How SARS-CoV-2, Fear of Contagion, and Lockdown Measures Impacted Attendance and Clinical Activity During February and March 2020 at an Urban Emergency Department in Milan. (27th October 2021) - Franchini, Stefano; Spessot, Marzia; Landoni, Giovanni; Piani, Cecilia; Cappelletti, Chiara; Mariani, Federica; Mauri, Simona; Taglietti, Maria Vittoria; Fortunato, Manuela; Furlan, Federico; Guglielmi, Barbara; Setti, Eleonora; et al.
ABSTRACT: Objectives: An unprecedented wave of patients with acute respiratory failure due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease 2019 (COVID-19) hit emergency departments (EDs) in Lombardy, starting in the second half of February 2020. This study describes the direct and indirect impacts of the SARS-CoV-2 outbreak on an urban major-hospital ED. Methods: Data regarding all patients diagnosed with COVID-19 presenting from February 1 to March 31, 2020, were prospectively collected, while data regarding non-COVID patients presenting within the same period in 2019 were retrospectively retrieved. Results: ED attendance dropped by 37% in 2020. Two-thirds of this reduction occurred early after the identification of the first autochthonous COVID-19 case in Lombardy, before lockdown measures were enforced. Hospital admissions of non-COVID patients fell by 26%. During the peak of COVID-19 attendance, the ED faced an extraordinary increase in: patients needing oxygen (+239%) or noninvasive ventilation (+725%), transfers to the intensive care unit (+57%), and in-hospital mortality (+309%), compared with the same period in 2019. Conclusions: The COVID-19 outbreak determined an unprecedented upsurge in respiratory failure cases and mortality. Fear of contagion triggered a spontaneous, marked reduction of ED attendance, and, presumably, some as yet unknown quantity of missed or delayed diagnoses for conditions other than COVID-19.